A clinical study of ectopic pregnancy at a tertiary care centre in Telangana, India - Samantaray, Subha Ranjan; Mohapatra, Ipsita; Vivekanada, Achanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ectopic pregnancy (EP) is a life-threatening obstetrics emergency in early trimester, associated with a high morbidity and mortality if not timely intervened. High index of clinical suspicion is required for early diagnosis, specifically in women presenting with amenorrhoea, pain abdomen and vaginal bleeding. Aim of this study is to determine the incidence, risk factors, clinical presentation, management and outcome of ectopic pregnancy. Methods: This retrospective observational study was conducted in the department of obstetrics and gynaecology, at Prathima institute of medical sciences, Telangana from July 2012 to June 2019, for a period of 7 years. A total of 53 cases of ectopic pregnancy were analyzed for parameters like age, gravidity, gestational age, risk factors, clinical presentation, management and morbidity. Results: Incidence of ectopic pregnancy was 5.3 per thousand deliveries. Majority of cases were in age group of 20 to 25 years (52.8%) and were gravida 3 and above (68%). The commonest risk factors identified were history of previous pelvic surgeries (37.7%) followed by history of abortion (18.8%). Commonest symptoms were abdominal pain (90.6%), amenorrhoea (75.5%) and vaginal bleeding (47.2%). Only 41.5 % of cases had triad of symptoms. Fallopian tube (92.4%), specifically ampulla (62.3%) was the most frequent site affected. About 73.6% cases presented with ruptured tube. Surgery (94.3%) was the mainstay of therapy. Conclusions: ectopic pregnancy is a life-threatening emergency, early diagnosis and treatment will improve the prognosis.